STUDI TENTANG KREATIVITAS GURU DALAM KEGIATAN PEMBELAJARAN ILMU STATIKA DAN TEGANGAN PADA SMK NEGERI JAKARTA - Nurma Lestari; Amos Neolaka; Nira Nasution (LPPM Universitas Negeri Jakarta, 2015)
This study aims to determine the operational levels Teacher Creativity In lessons activity of ilmu statika dan tegangan lesson in State SMK Jakarta. Place of research in State SMK Jakarta. The research method was descriptive survey. The sample is 5 teacher who teaching ilmu statika dan tegangan lesson in ten class. Teacher creativity in lessons activity data obtained through a questionnaire with Likert scale. Test results showed that 52 items found valid and reliable statement.The result of the research is teacher creativity in lessons have done quite creative. The conclusion is the higher teacher creativity in lessons activity it will assist students more focus and interest in lessons activity and result achievement as expected